Multi-spacecraft constraints on relativistic solar energetic particle transport in the widespread 28 October 2021 event - Lavasa, E.; Lang, J. T.; Papaioannou, A.; Strauss, R. D.; Mallios, S. A.; Hillaris, A.; Kouloumvakos, A.; Anastasiadis, A.; Daglis, I. A. (EDP Sciences, 2026)
Aims. We investigated the transport of solar energetic particles (SEPs) during the relativistic widespread event of 28 October 2021, quantifying the role of parallel and perpendicular diffusion and constraining the spatial extent of the injection region.
Methods. We employed inverse modeling of particle focused transport and 2D numerical simulations including cross-field diffusion. Multi-spacecraft observations from STEREO-A, Solar Orbiter, and near-Earth spacecraft are used to reproduce particle intensity profiles and anisotropies across a wide range of electron and proton energies. Simulated flux profiles are compared across different heliolongitudes to derive consistent transport parameters.
Results. The analysis yields parallel mean free paths within or slightly above the Palmer consensus range, and perpendicular mean free paths that correspond to ∼1–3% of parallel for electrons and ∼5–10% for protons. The injection region is found to be relatively narrow (≤20°), and decreasing with particle rigidity. Multipoint simulations indicate that the observed flux and anisotropy profiles can only be reproduced by a narrow injection region and significant cross-field diffusion. Electron and proton release times align well with the parent X1.0 flare and associated coronal mass injection (CME) onset, indicating that a compact acceleration region coupled with efficient interplanetary diffusion governed the event’s broad spatial extent.